ANALISIS PERLINDUNGAN HUKUM BAGI PERAWAT YANG MELAKUKAN TINDAKAN MEDIS DALAM KEADAAN DARURAT ATAS DASAR LIMPAHAN DOKTER - Suryanti, Reny; Susilo, Avrilya Iqoranny (Politeknik Kesehatan Kemenkes Bengkulu, 2023)
In carrying out their duties, nurses often carry out medical procedures that are not within their competence, so they require legal protection, especially in emergency situations. Legal protection is the right of nurses in providing health services, regulated in Article 27 paragraph (1) of Law No. 36 of 2009. The problem of this research is how legal protection is for nurses' medical actions based on the doctor's authority and why is legal protection necessary for nurses who carry out actions, medical emergency. By using qualitative methods and a juridical-empirical approach and using the Post-Positivism paradigm. The research was conducted at the Bengkulu City Regional Hospital. The results of the research and discussion show that legal protection for nurses who carry out medical procedures in emergency situations on the basis of a doctor's appointment is legally protected for nurses who have a registration certificate, work permit, and work in accordance with competency, service standards, professional standards, and standard operational procedures. As well as defense and assistance as long as the nurse is registered as a PPNI member and accompanied by a lawyer. The need for legal protection for nurses who carry out medical procedures in emergency situations is due to the gap between das sein and das sollen. What is legally protected is when carrying out medical procedures on behalf of a doctor, on humanitarian grounds the nurse must carry out medical procedures in an emergency even without a doctor's assistance, because in practice nurses are faced with the situation of having to carry out medical procedures with humanitarian considerations.